2020
DOI: 10.1002/adtp.201900215
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Translation of Nanomedicine and Biomaterials for Cancer Immunotherapy: Progress and Perspectives

Abstract: Advances in immuno‐oncology have significantly improved cancer therapy outcomes. Unfortunately, potent responses to immunotherapy have only been achieved in subsets of patients. Nanomedicines and biomaterials have enormous potential for making immunotherapy work better in more patients, which has been suggested by a large number of preclinical studies. However, it remains unclear whether and how these materials will really benefit cancer patients treated by immunotherapy. Therefore, reviewing current clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 71 publications
0
44
0
Order By: Relevance
“…Moreover, strategies are needed to improve the effectiveness of nanomedicine therapy. This can be done via pharmacological and physical co-treatments to prime tumors for improved delivery and efficacy, via active targeting, via the use of multi-stage and/or stimuli-responsive nanocarrier materials, and via the combination of nanotherapeutics with immunotherapy 14 , which has already shown initial clinical success 15 . In this virtual special issue of Theranostics, 24 research and review articles are compiled which discuss approaches aimed at improving the therapeutic efficacy of cancer nanomedicine.…”
mentioning
confidence: 99%
“…Moreover, strategies are needed to improve the effectiveness of nanomedicine therapy. This can be done via pharmacological and physical co-treatments to prime tumors for improved delivery and efficacy, via active targeting, via the use of multi-stage and/or stimuli-responsive nanocarrier materials, and via the combination of nanotherapeutics with immunotherapy 14 , which has already shown initial clinical success 15 . In this virtual special issue of Theranostics, 24 research and review articles are compiled which discuss approaches aimed at improving the therapeutic efficacy of cancer nanomedicine.…”
mentioning
confidence: 99%
“…Investigators face many significant challenges in their efforts to reach clinical translation of their innovative medical technologies. The success rate for translation of newly engineered medical technologies into clinical practice is low [1][2][3][4]. Traversing the translational "valleys of death" (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Results demonstrated that three patients generated T cell responses against NY-ESO-1, two of which also showed responses against MAGE-A3 [ 18 ]. Recently, BioNTech announced a strategic collaboration with Regeneron to initiate the phase II clinical trial combining BNT111 with Regeneron Libtayo (cemiplimab), a fully humanized anti-PD-1 therapy in patients with anti-PD1-refractory/relapsed, unresectable Stage III or IV cutaneous melanoma [ 142 ].…”
Section: Clinical Overview Of Mrna Cancer Vaccinesmentioning
confidence: 99%